Salvianolic Acids: Potential Source of Natural Drugs for the Treatment of Fibrosis Disease and Cancer - Ma, Lunkun; Tang, Liling; Yi, Qian (Frontiers in Pharmacology, 2019)
Salvianolic acids, the most effective and abundant compounds extracted from salvia miltiorrhiza (Danshen), are well known for its good anti-oxidative activity. Danshen has been widely used as a traditional medicine to treat cardiovascular related diseases in China and other Asian countries for hundreds of years. Recently, more and more studies have demonstrated that salvianolic acids also have a good effect on the alleviation of fibrosis disease and the treatment of cancer. In vivo and in vitro experiments have demonstrated that salvianolic acids can modulate signal transduction within fibroblasts and cancer cells. It is discovered that the cancer treatment of salvianolic acids is not only because salvianolic acids promote the apoptosis of cancer cells, but also due to the inhibition of cancer-associated epithelial-mesenchymal transition processes. In this article, we review a variety of studies focusing on the comprehensive roles of salvianolic acids in the treatment of fibrosis disease and cancer. These perspectives about therapeutic potential of salvianolic acids highlight the importance of these compounds, which could be the novel and attractive drugs for fibrosis disease and cancer.